Artificial Intelligence Governance Beyond Borders: The EU AI Act’s Influence on Third Party Legal Frameworks and Regional Organizations - Musthafa, Annas Rasid; Arundhati, Gautama Budi (Review of European and Comparative Law, 2025)
This research examines the perspective and influence of the European Union’s Artificial Intelligence Act (EU AI Act) on AI regulation in third countries and regional organizations. Using a doctrinal legal method with statutory and comparative law approaches, the study finds that the EU AI Act is a binding regulation applicable to all EU Member States. It aims to improve the internal market by introducing horizontal regulations focused on human rights protection. The Act defines AI broadly as a family of technologies affecting all aspects of life and classifies AI systems by risk level to determine development and market standards. This framework influences third-country regulations through the Brussels Effect. De facto, global companies, including from the U.S. and China, comply with the EU AI Act to access its market. De jure, some countries adopt its provisions into their own legal frameworks. The EU AI Act also impacts regional organizations such as ASEAN, which incorporates elements of the Act into cooperative policy documents, reflecting a shared political commitment to responsible AI governance.